Social Determinants of Health and High-Risk Pregnancy among First-Trimester Antenatal Attendees in Belagavi District, Karnataka: A Cross-Sectional Study - Akshay A Kolakar; Mubashir Angolkar; Rajeshwari Guranavara; Mayank Singh; Anita Dalal (National Journal of Community Medicine, 2026)
Background: Maternal health is crucial for family and community well-being, yet high-risk pregnancies are common in India. Economic hardship, limited education, and insufficient social support increase complication risk. The purpose was to estimate the prevalence of high-risk pregnancies and to assess the association of social determinants of health with high-risk pregnancy in Belagavi district Methodology: A cross-sectional investigation was carried out from April to September 2025 in Belagavi district among 456 first-trimester pregnant women. High-risk pregnancy was defined as ≥1 pre-existing maternal, obstetric, or medical risk factor. Data on sociodemographic, social determinants of health, and obstetric history were collected, and associations with high-risk pregnancy were analysed using chi-square methods and multivariable logistic regression. Results: High-risk pregnancies accounted for 52.4%; financial strain, food insecurity, unreliable transportation, and moderate perceived safety were associated with higher risk. Independent predictors included professional/administrative household-head occupation, associated with lower odds (AOR = 0.067, 95% CI: 0.005-0.943); upper middle-class status (AOR = 5.13, 95% CI: 1.43-18.43); and moderate safety perception (AOR = 1.60, 95% CI: 1.03-2.46), both associated with higher odds. Conclusions: Household head occupation, economic status, and perceived safety were associated with pregnancy risk. Financial stability, healthcare access, and safer environments may be associated with lower high-risk pregnancy.